Knowledge, Attitude and Faculty Members’ performance on e-Learning in Tehran University of Medical Sciences - Aeen Mohammadi; Mitra Gharib; Mitra Zolfaghari; Rita Mojtahedzadeh; Sana Ahmadian (Journal of Medical Education and Development, 2016)
Introduction : E-learning is used in the worldwide in higher education to improve the quality of the learning experience by students; at the same time using this approach requires behavioral changes in the faculty members. One of the steps in the implementation and monitoring of e-learning, is audience analysis using techniques such as knowledge, attitude and practices (KAP). This study investigates the knowledge, attitude and faculty members’ performance of Tehran University of Medical Sciences (TUMS) on e-learning.